A comparison of the experimental and theoretical charge density distributions in two polymorphic modifications of piroxicam. Issue 41 (10th October 2016) - Lai, Felcia; Du, Jonathan J.; Williams, Peter A.; Váradi, Linda; Baker, Daniel; Groundwater, Paul W.; Overgaard, Jacob; Platts, James A.; Hibbs, David E.
Abstract : Experimental charge density analysis of two piroxicam polymorphs has found a redistribution of charge to a non-classical zwitterionic form. Abstract : Experimental charge density distribution studies of two polymorphic forms of piroxicam, β-piroxicam(1) and piroxicam monohydrate(2), were carried out via high-resolution single crystal X-ray diffraction experiments and multipole refinement. The asymmetric unit of(2) consists of two discrete piroxicam molecules, (2a) and(2b), and two water molecules. Geometry differs between(1) and(2) due to the zwitterionic nature of(2) which results in the rotation of the pyridine ring around the C(10)–N(2) bond by approximately 180°. Consequently, the pyridine and amide are no longer co-planar and(2) forms two exclusive, strong hydrogen bonds, H(3)⋯O(4) and H(2)⋯O(3), with bond energies of 66.14 kJ mol −1 and 112.82 kJ mol −1 for(2a), and 58.35 kJ mol −1 and 159.51 kJ mol −1 for(2b), respectively. Proton transfer between O(3) and N(3) in(2) results in significant differences in surface electrostatic potentials. This is clarified by the calculation of atomic charges in the zwitterion that shows the formally positive charge of the pyridyl nitrogen which is redistributed over the whole of the pyridine ring instead of concentrating at N–H. Similarly, the negative charge of the oxygen is distributed across the benzothiazine carboxamide moiety. The multipole derived lattice energy for(1) is −304 kJ mol −1 and that for(2) is −571 kJ mol −1, which is in agreement with the experimentally determined observations of higher solubility and dissolution rates of(1) compared to(2) .